THE USAGE OF SOCIAL NETWORKS IN TEACHING A FOREIGN LANGUAGE (American Journal of Pedagogical and Educational Research, 2023)
This article discusses how to use various intelligence technologies, Internet services, and social networks in teaching a foreign language. Facebook, being the world's largest social network, is given special attention. The great academic potential of the social network Facebook in the modernization of the educational process is also discussed in this article.